PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR SENAM KEBUGARAN JASMANI 2018 - Boby Arianto; Victor G Simanjuntak; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe issue in this study is that students' abilities in the 2018 physical fitness exercise material are lacking, resulting in boredom in learning activities and mistakes in practice. The goal of this research was to see if jigsaw cooperative learning improved learning results in class VII students at Junior High School 10 Pontianak for Physical Fitness Gymnastics 2018. Experimental Research was the research approach used. The study's research result are the Physical Fitness Gymnastics 2018 learning outcomes in the pretest (68.4) and posttest (80.28), with an average of the two (79.25) Standard Deviation is the difference between the lowest (65) and highest (88) values (3.94). The data was judged normal after the normality test with the Sig pretest value. Results The data homogeneity is declared homogeneous. If the T test result is 0.05 > 0.00, Ho is rejected. The use of the jigsaw type cooperative learning model had a substantial influence on improving the 2018 physical fitness exercise learning outcomes, according to the results of hypothesis testing, normalcy test, homogeneity test, and discussion.Keywords: Learning Outcomes, Physical Fitness Gymnastics 2018 , Cooperative Learning Type Jigsaw.